ANALISIS PENGARUH INTRUSI AIR LAUT TERHADAP AIR TANAH MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DI KELURAHAN TANJUNG KAPAL - Usman Malik; Anjas Priandani (Komunikasi Fisika Indonesia, 2022)
The effect of seawater intrusion on groundwater has been carried out in Tanjung Kapal Village, Rupat District by using the geoelectric method of the Schlumberger configuration. This study aims to determine the resistivity value, layer depth, thickness of the groundwater layer, determine the effect of seawater intrusion on groundwater and determine the water quality of residents' wells in Tanjung Kapal Village. This study took 5 samples and tested for pH and salinity parameters to determine water quality. The results of the research on line 1 had a resistivity value range between 1.13 - 0.04 Ωm depth of 0.70 - 36 m and the line 2 had a resistivity value range between 11.07 - 0.10 Ωm depth of 3.12 - 42 m. On line 1 is affected by seawater intrusion in layer 2 which has a resistivity value of 0.60 Ωm with a depth of 0.70 – 3.42 m. Line 2 is affected by seawater intrusion in layer 3 which has a resistivity value of 3.53 Ωm with a depth of 7.22 – 13.42 m. The influence of seawater intrusion causes the groundwater around the site to have brackish due to the relatively low salt content. Water quality based on pH parameters of 20% is not in accordance with quality standards and salinity parameters of 100% brackish water.